Strengthening one health in the future of the Caribbean through a regional community of practice - Marie-Jeanne Guenin; Séverine Thys; Eric M.C. Etter (One Health)
Forty-four experts in animal, plant, environmental and human health and in social sciences, formed a Caribbean community of practice and formulated an aspirational One Health future for the region, the obstacles and solutions to necessary changes to achieve that future.